2020
DOI: 10.3174/ajnr.a6404
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up MRI for Small Brain AVMs Treated by Radiosurgery: Is Gadolinium Really Necessary?

Abstract: BACKGROUND AND PURPOSE: Follow-up MR imaging of brain AVMs currently relies on contrast-enhanced sequences. Noncontrast techniques, including arterial spin-labeling and TOF, may have value in detecting a residual nidus after radiosurgery. The aim of this study was to compare noncontrast with contrast-enhanced MR imaging for the differentiation of residual-versus-obliterated brain AVMs in radiosurgically treated patients.MATERIALS AND METHODS: Twenty-eight consecutive patients with small brain AVMs (,20 mm) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Our group has also developed, over time, special sequences to further evaluate AVM obliteration by MRI, particularly for smallsized ones. 26…”
Section: Follow-upmentioning
confidence: 99%
“…Our group has also developed, over time, special sequences to further evaluate AVM obliteration by MRI, particularly for smallsized ones. 26…”
Section: Follow-upmentioning
confidence: 99%
“…49 Previous studies have demonstrated the utility of ASL in the evaluation of cerebral AVMs after treatment. [50][51][52][53][54] Leclerc et al compared the detectability of residual AVMs after SRS between non-contrast MRI consisting of TOF-MRA plus ASL and contrast-enhanced MRI including contrast-enhanced dynamic MRA plus post-contrast thin-slice 3D T1-weighted image (T1WI). 53 The noncontrast enhancement method was superior to the contrastenhanced methods for the detection of residual AVMs.…”
Section: Asl For Pediatric Neuroimagingmentioning
confidence: 99%
“…[50][51][52][53][54] Leclerc et al compared the detectability of residual AVMs after SRS between non-contrast MRI consisting of TOF-MRA plus ASL and contrast-enhanced MRI including contrast-enhanced dynamic MRA plus post-contrast thin-slice 3D T1-weighted image (T1WI). 53 The noncontrast enhancement method was superior to the contrastenhanced methods for the detection of residual AVMs. Heit et al compared the detection rate of residual AVMs between DSA and ASL and found that ASL was highly sensitive and specific in the detection of residual cerebral AVMs following SRS treatment.…”
Section: Asl For Pediatric Neuroimagingmentioning
confidence: 99%
“…Several MRI sequences, such as dynamic arterial spin-labeling MR angiography (MRA) and time-resolved contrast-enhanced MRA, have been reported to be useful for confirming AVM obliteration. 9,[22][23][24] It is true that such MRI sequences can detect microscopic remnants of AVMs, but they cannot quantify the progress of AVM obliteration or the therapeutic effect of SRS on AVM hemodynamics. Time-averaged 3D flow MRI is a quantitative MRI method using phase contrast (PC) techniques and allows for the noninvasive measurement of flow parameters, such as mean blood flow in vessels.…”
mentioning
confidence: 99%